2015
DOI: 10.1177/1461355715580914
|View full text |Cite
|
Sign up to set email alerts
|

Police responses to, and attitudes towards, male rape

Abstract: This article critically examines how the police respond to, and deal with, male rape victims. It also explores male rape victims’ experiences of the police. This is an issue that has been hugely overlooked in the growing literature on the treatment of sexual offences in the criminal justice system; that is, the treatment of adult male sexual assault and male rape complainants by police officers. To fill this gap in the literature, this article will explore findings from empirical studies of police attitudes al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 30 publications
0
40
0
2
Order By: Relevance
“…Gill [24] has conceived rape as a criminal act that is targeted at women in order to humiliate, debase, overwhelm and control them. But Javaid [25] also found that in England and Wales, male rape are usually underreported and are affected by the masculine nature of the police subculture.…”
Section: Characterizing Rape Victims and Offendersmentioning
confidence: 99%
“…Gill [24] has conceived rape as a criminal act that is targeted at women in order to humiliate, debase, overwhelm and control them. But Javaid [25] also found that in England and Wales, male rape are usually underreported and are affected by the masculine nature of the police subculture.…”
Section: Characterizing Rape Victims and Offendersmentioning
confidence: 99%
“…This is a particular problem, due to some research arguing that the police are homophobic and execute homophobic attitudes toward male rape victims (e.g., Stermac et al 1996;Lees 1997;Gregory and Lees 1999). Although these research studies were conducted over a decade ago, there is no recent research that examines the police responses to male rape victims, other than Rumney (2008Rumney ( , 2009), Abdullah-Khan 2008's recent monograph, and Javaid (2015cJavaid ( , 2016cJavaid ( , 2017.…”
Section: Setting the Scene: Understanding And Explaining Male Sexual mentioning
confidence: 99%
“…However, traits such as emotionality, submissiveness, homosexuality, and compliance are not in agreement with social norms pertaining to masculinity (Javaid, 2015b). Socially constructed ideas of masculinity are not consistent with construction of the rape victim as weak, feminine, and defenseless (Javaid, 2014a).…”
Section: Common Male Rape Myths In the Wider Communitymentioning
confidence: 88%
“…It is also important that the male rape myth that 'male rape happens only in prison' is eradicated because male rape occurring in the community may be overlooked. That said, it is vital to critically examine other male rape myths occurring in the community because they will ultimately influence the way state and voluntary agencies, regardless of their own professionalism, respond to and handle male rape victims (Javaid, 2015b).…”
Section: Rape In Institutions and Secondary Victimisationmentioning
confidence: 99%